PENGARUH MODAL SOSIAL DAN KOMPETENSI GURU TERHADAP KINERJA GURU DAN DIMODERASI BUDAYA ORGANISASI (Studi pada Guru SMP Negeri di Sub Rayon 02 Kota Semarang) - Budi Astuti, Cahyaning; Basiya, R (Jurnal Ilmiah Telaah Manajemen, 2017)
This study aims to examine and analyze the effect of social capital on the performance of teachers in the SMP Negeri in Sub Rayon 02 Semarang ; test and analyze the influence of teacher competence on the performance of teachers in the SMP Negeri in Sub Rayon 02 Semarang ; test and analyze the influence of organizational culture on performance of teachers in the SMP Negeri in Sub Rayon 02 Semarang ; test and analyze the influence of organizational culture on the relationship between social capital and the performance of teachers in the SMP Negeri in Sub Rayon 02 Semarang ; to test and analyze the influence of organizational culture on the relationship between teacher competence and performance of teachers in the SMP Negeri in Sub Rayon 02 Semarang. This type of research is explanatory research , using a quantitative approach . The population in this study is teachers of SMP Negeri in Sub Rayon 02 Semarang which amounts to 251 people . Samples were taken using nonprobability sampling techniques, from of 154 teachers. Mechanical analysis uses model test liner analysis , F test (ANOVA) , R² test and t test , regression test hypothesis testing moderation . The results showed that ; social capital has significant and positive on teacher performance; competence teacher has significant and positive on teacher performance; cultural organizations have significant and positive on teacher performance; organizational culture does not moderate the relation of social capital and teachers performance; organizational culture to moderate the relationship between the competence of teachers and teachers performance Key words : social capital , competence of teachers , teacher performance and organizational culture .